Rapid succession of uncultured marine bacterial and archaeal populations in a denitrifying continuous culture. (6th August 2014) - Kraft, Beate; Tegetmeyer, Halina E.; Meier, Dimitri; Geelhoed, Jeanine S.; Strous, Marc
Summary Marine denitrification constitutes an important part of the global nitrogen cycle and the diversity, abundance and process rates of denitrifying microorganisms have been the focus of many studies. Still, there is little insight in the ecophysiology of marine denitrifying communities. In this study, a heterotrophic denitrifying community from sediments of a marine intertidal flat active in nitrogen cycling was selected in a chemostat and monitored over a period of 50 days. The chemostat enabled the maintenance of constant and well‐defined experimental conditions over the time‐course of the experiment. Analysis of the microbial community composition by automated ribosomal intergenic spacer analysis (ARISA), Illumina sequencing and catalyzed reporter deposition fluorescence in situ hybridization (CARD‐FISH) revealed strong dynamics in community composition over time, while overall denitrification by the enrichment culture was stable. Members of the genera Arcobacter, Pseudomonas, Pseudovibrio, Rhodobacterales and of the phylum Bacteroidetes were identified as the dominant denitrifiers. Among the fermenting organisms co‐enriched with the denitrifiers was a novel archaeon affiliated with the recently proposed DPANN‐superphylum. The pan‐genome of populations affiliated to Pseudovibrio encoded a NirK as well as a NirS nitrite reductase, indicating the rare co‐occurrence of both evolutionary unrelated nitrite reductases within coexisting subpopulations.